2002
DOI: 10.1080/140154302760146952
|View full text |Cite
|
Sign up to set email alerts
|

Cordless amplifying system in classrooms. A descriptive study of teachers' and students' opinions

Abstract: This study investigated one possible method to diminish teachers' vocal loading and, consequently, voice problems. Thirty-three teachers used electric sound amplification in teaching for at least 1 week. Both the teachers (33) and the students (791) reported their opinions of the amplification in a questionnaire. Ninety-seven percent of the teachers reported easier voice production, 82% found improved vocal endurance. The need for repetition also diminished. Eighty-four percent of the students found listening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 17 publications
1
23
0
8
Order By: Relevance
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 81%
“…With regard to the point of view of the children, most of the teachers in the study reported that children became immediately used to the novelty, and they also benefitted from listening. Also this aspect is in agreement with some previous reports indicating that poor voice quality in teachers reduces the intelligibility of speech [14,15,24,25], while amplification both reduces the need for repetition and permits better concentration [15].…”
Section: Discussionsupporting
confidence: 81%
“…1,9,20,25,34 (Continued ) Amplification has shown to be beneficial in a number of studies with teachers and students. [15][16][17][44][45][46][47][48] Yiu 19 reported that teachers suggested amplifiers as a strategy to avoid voice problems. Voice care may include recommending the use of an amplifier or microphone.…”
Section: Swimmingmentioning
confidence: 99%
“…[9][10][11] Furthermore, teachers do not have voice complaints during vacation time but during the term. [11][12] Various acoustic changes have been found to take place after a vocally loading task, whether it is a loading test in a laboratory or a teacher's working day or an actor's theater performance. [13][14][15][16][17][18] Fundamental frequency (F0) and SPL have been found to be higher after loading, and the spectral tilt has also been found to be lower in females after loading.…”
Section: Introductionmentioning
confidence: 99%